Possible contamination of the Abrolhos reefs by Fundao dam tailings, Brazil – New constraints based on satellite data - Coimbra, Keyla Thayrinne Oliveira; Alcântara, Enner [UNESP]; de Souza Filho, Carlos Roberto (Elsevier, 2020)
The Fundão dam, located in Mariana city, Minas Gerais State, southeastern Brazil, collapsed in November 2015, causing the discharge of over 50 million m3 of iron ore tailings in the Doce river basin. The mud generated by the disaster was composed of fine particulates (silt and clay), which are more sensitive to wind dispersion. Based on laboratory analyses and hydrodynamic modeling, early research postulates the hypothesis that the mud discharged in the ocean traveled 10,000 km up north and may have reached the Abrolhos coral reefs. This research aims to investigate further this hypothesis based on broad-scale remotely sensed data. Satellite images were used to estimate the suspended particulate matter (SPM) in the coastal zone before, during, and after the dam collapse. Results indicate that higher concentrations of SPM appeared during and post-collapse and were restricted to the coastal zone and its shallower regions, including beaches. However, we demonstrate that under exceptional circumstances the wind blew to the north, carrying fine particulate material and potentially-toxic metals derived from the iron ore tailings towards the northeastern Brazilian coastline and possibly the reefs of the Abrolhos Bank.
Keywords: Abrolhos reefs; Fundão dam collapse; Mining; Remote sensing; Tailings